Efektivitas Model Problem Based Learning Berbantuan Board Game Ular Tangga Untuk Meningkatkan Hasil Belajar Peserta Didik - Putri Rosyada, Balqis; Erni; Izzatika, Amrina; Yuni Astiti, Niken; Yudisthira, Ardhi (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2025)
The problem based learning model assisted by games in the learning process is able to create fun learning activities and make it easier for students to understand the contents of the material. This study aims to determine the effectiveness of the application of the Problem Based Learning model assisted by the Snake and Ladder Board game to improve the science learning outcomes of grade VI students of Elementary School 1 Metro Timur. The method used is a quasi-experiment with a nonequivalent (pretest and posttest) control group design. The population in this study was 44 students with a sample taken of 44 students. Data collection techniques used tests and non-tests. Hypothesis testing using the N-Gain test produced an N-Gain score of 0.75 with an N-Gain interpretation of 75%. The results showed that the application of the Problem Based Learning model assisted by the Snake and Ladder Board game was effective in improving the science learning outcomes of grade VI students of Elementary School 1 Metro Timur.